2019
DOI: 10.1016/j.physio.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Taping reduces pain and improves disability in low back pain patients: a randomised controlled trial

Abstract: Kinesio Taping reduces pain and improves disability in Low Back Pain patients:a randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 38 publications
(61 reference statements)
1
40
1
1
Order By: Relevance
“…It shows that this area is not well known and clarification of how various KT applications could be used to support treatment patients with specific and unspecific spine disorders is required. The use of the tape provides an easy cost-effective feedback method for trainers, patients, and therapists to cue immediate changes in spine posture during sagittal plane movements [71].…”
Section: Discussionmentioning
confidence: 99%
“…It shows that this area is not well known and clarification of how various KT applications could be used to support treatment patients with specific and unspecific spine disorders is required. The use of the tape provides an easy cost-effective feedback method for trainers, patients, and therapists to cue immediate changes in spine posture during sagittal plane movements [71].…”
Section: Discussionmentioning
confidence: 99%
“…Tape tension is a key factor of the KT method [14]. One study showed that tape tension can improve proprioceptive feedback and facilitate correct posture and movement, even after removal of the tape [25]. However, another study found that the tension might have reversal effects on functional performance [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to conclude that the effect of KT application is simply due to the placebo effect because its effects on pain, disability, and functional performance have been controversial over a decade [1,3,4,13,18,19,21,23,25,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were twenty-three RCTs related to conditions of the lumbar spine and abdominal wall, with all but one assessing KT (Appendix 2 File: Appendix 2G). One addressed KT for acute low back pain [136], two investigated KT for back pain in the setting of lumbar disc herniation [137,138], two investigated KT for pregnancy related low back pain [139,140], one RCT investigated postpartum diastasis recti abdominis [141], and sixteen investigated KT for chronic low back pain, [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157]. One study evaluated rigid taping for sacroiliac joint dysfunction [158].…”
Section: Lumbar Spinementioning
confidence: 99%